SYSTEM SALES OF AGRICULTURAL TOOLS WITH APPLICATIONS IN PT . STINDO MICROSOFT ACCESS APPLICATION - Eko Arief Hidayat; Cut Asiana Asiana Gemawaty, Skom, MMSi (Jurnal Sistem Informasi, 2002)
PT. STINDO is a company which is engaged in agro-business, especially sales of agricultural equipment. This company is helping the farmers and entrepreneurs in the field of agriculture, this company has not been computerized, thus allowing the occurrence of errors in reporting the sale and purchase. So re -writing will be done, because the preparation of reports made one by one based on existing transactions. Obviously this would increase jobs and take a long time. By knowing the problemsÂ  that exist, the proposed system is by using the computer to process data particularly relating to the sale of agricultural tools.Â